2019
DOI: 10.1136/bmjopen-2019-029809
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in relation to disordered eating, body size and weight perception: a cross-sectional study of a Norwegian adolescent population: the HUNT Study

Abstract: ObjectiveWe conducted a population-based study on a sample of more than 7000 adolescents where we examined the associations between suicidal ideation (SI) and disordered eating (DE) and its related traits.DesignCross-sectional.SettingsData were derived from two Norwegian population-based cohorts, the Young-HUNT1 (1995–1997) and Young-HUNT3 (2006–2008) from the county of Nord-Trøndelag, Norway.ParticipantsA total of 7268 adolescents (15–19 years) who had completed self-reported questionnaires including items on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(44 reference statements)
2
4
1
Order By: Relevance
“…That being said, our findings revealed that patients presenting with acute symptom onsets were more likely to endorse suicidal ideation and/or self- harm than their chronic onset peers. This is congruent with previous studies indicating an association between suicidal ideation and/or self-harm and disordered eating [41], and indicates that symptom duration may be an important factor in further understanding this link. These potential associations have important implications for treatment, as youth presenting with acute symptoms of ARFID may need more thorough and timely evaluation of safety concerns even though their weights may not be as low as their chronic counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…That being said, our findings revealed that patients presenting with acute symptom onsets were more likely to endorse suicidal ideation and/or self- harm than their chronic onset peers. This is congruent with previous studies indicating an association between suicidal ideation and/or self-harm and disordered eating [41], and indicates that symptom duration may be an important factor in further understanding this link. These potential associations have important implications for treatment, as youth presenting with acute symptoms of ARFID may need more thorough and timely evaluation of safety concerns even though their weights may not be as low as their chronic counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with their female counterparts, adolescent boys who overestimated their body size quite consistently showed higher odds for MD. In line with previous findings,6 we found higher male vulnerability to MD across all weight concern/dieting groups. Since weight concern/dieting groups were defined based on BMI, the higher male vulnerability cannot be solely related to individuals’ BMI.…”
Section: Discussionsupporting
confidence: 93%
“…Preventing obesity has however, proved difficult 1–3. To lose weight, many adolescents resort to dieting; whose effectivity and long-term health consequences are debated 4–7. In order to strive to achieve (or maintain) normal weight, it is necessary for individuals, to have awareness of their own body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicidal ideation is common among adolescents, present in about 17.5% of the middle school students in China [1] and about 17.7% of adolescents in the United States [3]. Suicidal ideation has been found to be significantly associated with suicidal attempt, depressiveness, anxiety, disordered eating, and so on [4,5,6,7]. To sustain improvements in management and prevention initiatives, we need to identify and understand the risk and protective factors associated with suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%